Rib stress injuries in the 2012-2016 (Rio) Olympiad: a cohort study of 151 Australian Rowing Team athletes for 88 773 athlete days - Harris, R.; Trease, L.; Wilkie, K.; Drew, M. (British Journal of Sports Medicine, 2020)
Aim: To describe the demographics, frequency, location, imaging modality and clinician-identified factors of rib stress injury in a cohort of elite rowers over the Rio Olympiad (2012-2016).